Direct measurement of electron beam quality conversion factors using water calorimetry. Issue 11 (9th October 2015) - Renaud, James; Sarfehnia, Arman; Marchant, Kristin; McEwen, Malcolm; Ross, Carl; Seuntjens, Jan
Abstract : Purpose: In this work, the authors describe an electron sealed water calorimeter (ESWcal) designed to directly measure absorbed dose to water in clinical electron beams and its use to derive electron beam quality conversion factors for two ionization chamber types. Methods: A functioning calorimeter prototype was constructed in‐house and used to obtain reproducible measurements in clinical accelerator‐based 6, 9, 12, 16, and 20 MeV electron beams. Corrections for the radiation field perturbation due to the presence of the glass calorimeter vessel were calculated using Monte Carlo (MC) simulations. The conductive heat transfer due to dose gradients and nonwater materials was also accounted for using a commercial finite element method software package. Results: The relative combined standard uncertainty on the ESWcal dose was estimated to be 0.50% for the 9–20 MeV beams and 1.00% for the 6 MeV beam, demonstrating that the development of a water calorimeter‐based standard for electron beams over such a wide range of clinically relevant energies is feasible. The largest contributor to the uncertainty was the positioning (Type A, 0.10%–0.40%) and its influence on the perturbation correction (Type B, 0.10%–0.60%). As a preliminary validation, measurements performed with the ESWcal in a 6 MV photon beam were directly compared to results derived from the National Research Council of Canada (NRC) photon beam standard water calorimeter. These two independent devices were shown to agree well within the 0.43% combined relative uncertainty of the ESWcal for this beam type and quality. Absorbed dose electron beam quality conversion factors were measured using the ESWcal for the Exradin A12 and PTW Roos ionization chambers. The photon‐electron conversion factor, k ecal, for the A12 was also experimentally determined. Nonstatistically significant differences of up to 0.7% were found when compared to the calculation‐based factors listed in the AAPM's TG‐51 protocol. General agreement between the relative electron energy dependence of the PTW Roos data measured in this work and a recent MC‐based study are also shown. Conclusions: This is the first time that water calorimetry has been successfully used to measure electron beam quality conversion factors for energies as low as 6 MeV ( R 50 = 2.25 cm).